Economics of air transportation proceedings of the 7th World Airports Conference organized by the Institution of Civil Engineers and held in London on 24-26 May 1983. (Thomas Telford, 1984)
Focusing on the economics of air transportation, these papers highlight airport developments, deregulation, and financing. The airports, airlines, and aircraft involved are discussed, and key issues are focused on.